5D Entanglement in Star Polymer Dynamics. Issue 11 (13th September 2018) - Korolkovas, Airidas
Abstract: Star polymers are within the most topologically entangled macromolecules. For a star to move the current theory is that one arm must retract to the branch point. The probability of this event falls exponentially with molecular weight, and a quicker relaxation pathway eventually takes over. With a simulation over a hundred times faster than earlier studies, it is demonstrated that the mean square displacement scales with a power law 1/16 in time, instead of the previously assumed zero. It suggests that star polymer motion is the result of two linear relaxations coinciding in time. By analogy to linear polymers, which reptate with a random walk embedded in a 3D network, we show that star polymers relax by a random walk in a 5D network. Abstract : The theory of entangled star polymers held up until now is shown to break down for very long chains. A new simulation method is proposed, running over 100 times faster than any supercomputer attempt at this problem so far. The discovered terminal relaxation is a 1D random walk, confined by a 5D topological network.